Dictionary of Indian tongues [electronic resource] : containing most of the words and terms used in the Tshimpsean, Hydah, & Chinook, with their meaning or equivalent in the English language. (Victoria, V.I. [B.C.] : Hibben & Carswell, 1865)
Cover title. Electronic reproduction. Mode of access: Internet. 44